83.8k views
0 votes
12(2a-3)=-4a+5
what is the answer

User Aabdulahad
by
5.3k points

1 Answer

2 votes

12(2a-3)=-4a+5

Remember to follow PEMDAS. Note the equal sign, what you do to one side, you do to the other.

First, distribute 12 to all terms within the parenthesis

12(2a) = 24a

12(-3) = -36

24a - 36 = -4a + 5

Add 4a to both sides, and add 36 to both sides

24a (+4a) - 36 (+36) = -4a (+4a) + 5 (+36)

24a + 4a = 5 + 36

Simplify

28a = 41

Isolate the a. Divide 28 from both sides

28a/28 = 41/28

a = 41/28

Simplify a

a = 1.46 (simplified)

hope this helps

User NearHuscarl
by
5.6k points